Effect of Al doping on the photocatalytic activity of ZnO nanoparticles decorated on CNTs and graphene: Solvothermal synthesis and study of experimental parameters. (1st March 2021) - Ahmad, Irshad; Shukrullah, Shazia; Ahmad, Mukhtar; Ahmed, Ejaz; Naz, Muhammad Yasin; Akhtar, Muhammad Shoaib; Khalid, N.R.; Hussain, Abid; Hussain, Iqbal
Abstract: With the motive of the improvement of the photocatalytic activity in the visible region and high inhibition of electron-hole pairs recombination rate, we presented a facile single step solvothermal route synthesized pure ZnO, Al doped ZnO, Al doped ZnO/CNTs and Al doped ZnO/graphene composite using ethylene glycol as solvent and reducing agent. The as-synthesized photocatalysts were characterized by XRD, SEM, TEM, EDX, BET, UV–Vis DRS, PL, transient photocurrent response and EIS techniques. The experimental results for the photocatalytic Congo red degradation confirmed the successful incorporation of Al, CNTs and graphene into the lattice of ZnO and showed that Al doped ZnO/graphenecomposite revealed the highest photocatalytic activity of 100% within 60 min of simulated sunlight irradiation compared with pure ZnO, Al doped ZnO and Al doped ZnO/CNTs. The effect of operational parameters such as graphene loading, catalyst dose, initial pH, initial dye concentration, light intensity, oxidants, cations and anions on the photocatalytic activity of the optimum photocatalyst (Al doped ZnO/graphene) was also studied. The results of the operational parameters verified that 50 mg/L of Congo red could be completely degraded at graphene loading: 7 wt%, initial pH: 9, light intensity: 300 W/m 2, catalyst dose: 0.7 g/L over 50 min sunlight irradiation. Under the effect of optimum operational conditions, five times recycle experiments revealed negligible decline in the degradation efficiency of Al doped ZnO/graphene catalyst and confirmed its efficient reusability and stability. Graphical abstract: Image 1 Highlights: Al-ZnO based CNTs/graphene composite were prepared. Highest charge separation attained for Al doped ZnO/graphene. Al doped ZnO showed maximum photocatalytic activity.